Assessing the impact of drought stress on grasslands using multi-temporal SAR data of Sentinel-1: a case study in Eastern Cape, South Africa. (13th July 2020) - Abdel-Hamid, Ayman; Dubovyk, Olena; Graw, Valerie; Greve, Klaus
ABSTRACT: Grasslands are a major component of the natural vegetation in South Africa, it covers almost one-third of the country's land surface. The current study focuses on assessing the impact of drought stress on communal and commercial grasslands in Eastern Cape Province using multi-temporal analysis of Sentinel-1 SAR data. Data analysis included retrieval of biophysical parameters of grasslands using Sentinel-1 SAR backscattering coefficients. Correlation analysis was performed between SAR data and NDVI values derived from Landsat-8 optical data. A linear mixed-effects regression analysis was performed for detecting the impact of drought on communal and commercial grasslands during a drought and non-drought growing seasons. Our results indicate that vegetation dynamics in grasslands in the study area are highly responsive to the climatic fluctuations. A significant correlation between backscattering coefficients of Sentinel-1 SAR data (VH and VV) and NDVI was observed for both communal and commercial grasslands (R 2 = 0.89). Results also demonstrated that communal grasslands are more affected by drought impact than commercial grasslands. In commercial grasslands, management activities can improve the growing conditions of grasslands, reduce the impact of drought, and subsequently increase the resilience and productivity of this ecosystem.